Dielectric response analysis of mineral oil immersed transformer, Natural Ester(FR3) immersed transformer, and palm oil immersed transformer - Maneerot, Sakda; Nimsanong, Phethai; Siriworachanyadee, Jompatara; Leelajindakrairerk, Monthon; Jariyanurat, Kittipod; Pattanadech, Norasage (My University, 2019)
Currently alternative liquid insulation such as natural ester (FR3) is widely used as distribution transformer insulation because it provides outstandingly dielectric characteristics and natural friendly including highly affordable fire safety. Besides, palm oil is interesting liquid insulation for such transformers because of its distinguish dielectric properties. To analyze the dielectric properties of insulating material, polarization and depolarization current (PDC) measurement is one of the widely accepted non-destructive test technique. This paper presents the dielectric response analysis for the insulation system of a mineral oil immersed transformer, a natural ester (FR3) immersed transformer, and a palm oil immersed transformer by analyzing PDC test results. Three identical single phase transformers with 22kV/460V 30 kVA rated were designed and constructed. The first transformer was fully filled with mineral oil. The second and the third transformer was fully filled with natural ester (FR3) and palm oil respectively. After finishing the construction process, PDC measurement technique was applied for these transformers. The PDC measurement were performed for three case studies as follows: 1) dielectric response for the insulation between high voltage winding and low voltage winding, 2) dielectric response of high voltage winding insulation and low voltage connected to ground 3) dielectric response of high voltage and low voltage winding insulation by which the high voltage lead was connected to the low voltage lead. From the test results, it can be concluded that the dielectric response of the insulation system of the mineral oil immersed transformer was obviously different compared with that of the natural oil (FR3) immersed transformer and the palm oil immersed transformer. Moreover, the PDCs obtained from the tests were also analyzed and reported in this paper.
Keywords: Depolarization current; Dielectric response analysis; Mineral oil; Natural ester; Palm oil; Polarization current